1997
DOI: 10.1007/s004010050660
|View full text |Cite
|
Sign up to set email alerts
|

Internexin, MAP1B, and nestin in cortical dysplasia as markers of developmental maturity

Abstract: Cortical dysplasias (CD) are characterized histologically by disorganized cortical lamination and abnormally shaped neurons. We hypothesized that neurons within CD have failed to differentiate fully and may express proteins such as cytoskeletal elements characteristic of immature cells. Disrupted expression of certain cytoskeletal proteins, which have been implicated in neuronal polarity, process outgrowth, and migration, could result in disorganized cortical lamination. Thus, we probed two CD subtypes, focal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
67
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 23 publications
6
67
0
Order By: Relevance
“…Because at that time, GFAPd was only described in SVZ astrocytes (Roelofs et al, 2005), an area in which neural progenitors are located, we put forward the idea that the GFAPd subpopulation of balloon cells retains a progenitor phenotype or represents an influx of newly generated astrocytes from the SVZ. Several studies provided evidence that balloon cells in focal cortical dysplasia retain an embryonic phenotype and are derived from radial glial cells (Crino et al, 1997;Mizuguchi et al, 2002;Sisodiya et al, 2002;Thom et al, 2005). The fact that we found GFAPd expression in radial glia during brain development supports this view.…”
Section: Research Articlesupporting
confidence: 77%
“…Because at that time, GFAPd was only described in SVZ astrocytes (Roelofs et al, 2005), an area in which neural progenitors are located, we put forward the idea that the GFAPd subpopulation of balloon cells retains a progenitor phenotype or represents an influx of newly generated astrocytes from the SVZ. Several studies provided evidence that balloon cells in focal cortical dysplasia retain an embryonic phenotype and are derived from radial glial cells (Crino et al, 1997;Mizuguchi et al, 2002;Sisodiya et al, 2002;Thom et al, 2005). The fact that we found GFAPd expression in radial glia during brain development supports this view.…”
Section: Research Articlesupporting
confidence: 77%
“…These findings are consistent with previous reports that mRNA for all neuronal filaments is increased in dysplastic neurons in FCD. 33,34 Our microarray study also demonstrated a dysregulation of other neurofilament genes in cytomegalic neurons of FCD (M. Sheldon and colleagues, unpublished data). These results, however, require further analysis that is beyond the scope of this study.…”
Section: Discussionmentioning
confidence: 50%
“…Both these tissues appeared normal. Dysplastic neurons are known to contain large amounts of several intermediate filaments, [33][34][35] although these proteins are not unique to abnormal neurons. In contrast, this NF-H antibody labeled almost exclusively cytomegalic neurons in our specimens.…”
Section: Neurofilament Heavy Chain Is a Marker Of Cytomegalic Neuronsmentioning
confidence: 99%
“…Mixed seizure types may develop in the same patient. FCD regions are highly epileptogenic as determined by intraoperative electrocorticography [3,18]. Seizures in those patients with CD are particularly difficult to control with conventional antiepileptic drugs (AEDs) and many individuals will require surgical intervention.…”
Section: Epilepsy In Cortical Dysplasiasmentioning
confidence: 99%